Seers who unmask illusion : In conversation with Thomas Merton and Henri J.M. Nouwen - Marchinkowski, George; Langerman, Peter (Stellenbosch Theological Journal, 2023)
As humanity seeks to redefine its relationships with technology, the earth and ultimate reality, the mystics can assist in discerning a way forward. How can we live at peace in a rapidly changing and technologically advancing world? Will these redefined relationships facilitate human flourishing or cause alienation? Twentieth century mystics Thomas Merton and Henri J. M. Nouwen believed that the conversation began with confronting illusion. The illusions human beings construct begin in the Self (with the false personas we create) but extend to the collectives we relate to. Merton and Nouwen were mystics and social critics, from a starting point of contemplation, representing ‘Christ, the challenger and disturber of human illusion.’ This article seeks to showcase their contribution while outlining some spiritual practices seekers might adopt to navigate our complex and constantly transforming milieu.